Draf Undang-Undang Perkawinan Indonesia: Basis Filosofis dan Implikasinya dalam Butir-Butir UU - Khoirudin Nasution (Unisia, 2003)
As can be seen from the draft of the Law of Marriage (RUU Perkawinan), some new ideas of marital aspects have been included in its chapters and articles. However, in some areas, more critical suggestions are still needed to make the draft more relevant with the social dynamics. This article tnes to analyze three aspects of the draft, polygamy, status and authority of spouses, and the last, problems relate divorce. Further, the article also gives the solution for those areas.